THE ROLE OF KARAKUL BREEDING IN THE ECONOMY AND DEVELOPMENT PROSPECTS - Shodiyev Bekzod Tulkinovich; Abdieva Dilfuza Kurbanovna (Modern American Journals, 2025)
The article explores the development of the karakul breeding industry in our country and its role in agriculture. It analyzes issues related to increasing the production volume of karakul products, improving breeding practices, efficient use of pastures, and processing and exporting products. A SWOT analysis of internal and external factors is conducted to ensure the sustainable development of the industry, and strategic development directions are identified. Based on the analysis, specific measures are proposed to leverage strengths, address weaknesses, and manage risks. It is emphasized that the proposed approach contributes to the long-term sustainable development of the karakul breeding sector.
Keywords: Karakul breeding, agriculture, pasture utilization, SWOT analysis, ecological adaptability, export potential, competitiveness, technology implementation, sustainable development, karakul pelts, international cooperation, climate change.